Spatially explicit modeling of schistosomiasis risk in Eastern China based on a synthesis of epidemiological, environmental and intermediate host genetic data - Schrader, Matthias; Hauffe, Torsten; Zhang, Zhijie; Davis, George M.; Jopp, Fred; Remais, Justin V.; Wilke, Thomas; Justus Liebig University Giessen (My University, 2013)
Schistosomiasis is considered the second most devastating parasitic disease after malaria. In China, it is transmitted to humans, cattle and other vertebrate hosts by a single intermediate snail host. It has long been suggested that the close co-evolutionary relationship between parasite and intermediate host makes the snail a major transmission bottleneck in the disease life cycle. Here, we use a novel approach to model the disease distribution in eastern China based on a combination of epidemiological, ecological, and genetic information. We found four major high risk areas for schistosomiasis occurrence in the large lakes and flood plain regions of the Yangtze River. These regions are interconnected, suggesting that the disease may be maintained in eastern China in part through the annual flooding of the Yangtze River, which drives snail transport and admixture of genotypes. The novel approach undertaken yielded improved prediction of schistosomiasis disease distribution in eastern China. Thus, it may also be of value for the predictive modeling of other host- or vector-borne diseases.
Keywords: ddc:570